Kinerja Keuangan Koperasi Produksi Susu (KPS) Bogor Sebelum dan Selama Penyakit Kuku dan Mulut - Firman, Achmad; Mauludin, Mochamad Ali; Kusmayadi, Tendy (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Dairy cooperatives are a forum for dairy farmers to distribute their fresh milk production. If an extraordinary event occurs in dairy farmers, it can affect the performance of dairy cooperatives, such as an outbreak of foot and mouth disease (FMD). The aim of this study was to analyze the cooperative's milk production performance and the cooperative's financial performance before and during hoof and mouth disease. The analytical method used is basic statistics to see the performance of milk production, while the financial performance analysis uses the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises (KUKM) of the Republic of Indonesia Number 06/Per/Dep.6/IV/2016 and the key performance index (KPIs). The research results showed that there was a 27% decrease in milk production during the foot and mouth disease (FMD) outbreak which was caused by the large number of deaths of productive dairy cows. The financial performance of KPS Bogor has a KPIs value before PMK of 73.21 and during FMD of 67.50 or both of these values are in the Fair category. However, it was seen that there was a decline in the value of financial performance before and during the FMD.